Teachers’ Attitudes and Practices Concerning the Development of Students’ Cultural Diversity Awareness and Intercultural Communicative Competence: A Pilot Study in an International School in Hungary - Dogan Ger, Songul (Working Papers in Language Pedagogy, 2020)
As a result of globalization and mobility around the world, the need for effective communication in multicultural contexts has brought the recognition of culture teaching into the field of foreign language teaching. On top of teaching language skills, teachers are now expected to develop students’ cultural diversity awareness (CDA) and intercultural communicative competence (ICC). This study describes a study aimed to pilot a research instrument designed to be used later in the author’s larger-scale research on the development of students’ CDA and ICC. The pilot study is based on in-depth interviews with three teachers. The interview study aimed to investigate how teachers perceive the concept of culture, what they think about culture teaching and how they develop CDA and ICC in their practices of teaching English. Findings indicate that teachers are aware of cultural diversity and they have positive attitudes towards learning and teaching different cultures. However, they need to be encouraged to teach cultures more explicitly in various ways recommended in the theoretical background. In terms of piloting the research instrument, findings also show that the interview schedule successfully probes teachers’ attitudes and practices about the development of CDA and ICC.